2018
DOI: 10.1080/09638288.2018.1485181
|View full text |Cite
|
Sign up to set email alerts
|

Effects of daily inspiratory muscle training on respiratory muscle strength and chest wall regional volumes in haemodialysis patients: a randomised clinical trial

Abstract: www.ClinicalTrials.gov ; study number: NCT02599987; name of trial registry: IMT in Patients with End-stage Renal Disease. Implications for rehabilitation Muscular impairment in chronic kidney disease patients results from a series of common alterations, affecting respiratory muscles. Patients with chronic kidney disease have low values of diaphragmatic thickness. The daily inspiratory muscle training (IMT) or breathing exercise over a period of 8 weeks provided increased respiratory muscle strength. The daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 32 publications
1
24
0
6
Order By: Relevance
“…Selection bias. Because it was a requirement of the review that included studies be RCTs, most studies had adequate randomization or participant allocation (12,14,16,18,23,41,45,50,55,60,62,74,76,77,81,84,90,92). Concealment of the randomization method was described in only 18 of the included studies (12,14,16,18,23,41,45,50,53,55,60,62,74,76,77,81,84,92).…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Selection bias. Because it was a requirement of the review that included studies be RCTs, most studies had adequate randomization or participant allocation (12,14,16,18,23,41,45,50,55,60,62,74,76,77,81,84,90,92). Concealment of the randomization method was described in only 18 of the included studies (12,14,16,18,23,41,45,50,53,55,60,62,74,76,77,81,84,92).…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…Because it was a requirement of the review that included studies be RCTs, most studies had adequate randomization or participant allocation (12,14,16,18,23,41,45,50,55,60,62,74,76,77,81,84,90,92). Concealment of the randomization method was described in only 18 of the included studies (12,14,16,18,23,41,45,50,53,55,60,62,74,76,77,81,84,92). One study allocated participants to intervention or control group by dialysis shift, which appeared to provide a random representation of the whole sample, as there was no significant difference in baseline characteristics between groups (22).…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…Potential mechanisms that may explain impaired respiratory function in patients undergoing MHD include not only reduced respiratory muscle strength but also volume overload causing lung congestion and chronic inflammation underlying telomere shortening, which has been shown to lead to senescence of lung alveolar and endothelial cells [60,61]. Regular exercise has been shown to reduce the decline in pulmonary function in CKD [21,59]; in particular, studies designed specifically to strengthen the respiratory muscles have reported improved respiratory muscle strength and pulmonary function [59,[62][63][64]. Pomidori et al [65] reported improvements in respiratory muscle strength after a 6-month home walking program in MHD subjects, but no changes in FVC or FEV 1 .…”
Section: Discussionmentioning
confidence: 99%
“…De acordo com a National Kidney Fundation, a doença renal crônica (DRC) é caracterizada por alterações na função ou estrutura renal durante 3 meses ou mais, de caráter assintomático e progressivo, levando a perda funcional dos rins, sendo necessário realizar terapia substitutiva, por meio de diálise peritoneal ou hemodiálise, estabelecendo um equilíbrio metabólico e nutricional 1,2 .…”
Section: Functional Capacity Analysis Using the Six Minute Walk Test (6mwt) In Chronic Renal Patients Introduçãounclassified
“…A doença renal apresenta elevadas taxas de sobrevida, entretanto, é considerada uma doença altamente intrusiva devido às complicações e restrições que podem proporcionar, juntamente com a incerteza do seu prognóstico, esses fatores são somados e potencializados devido a instabilidade familiar, pessoal e laboral no qual o doente se encontra 3,6 . A DRC apresenta 5 estágios os quais são classificados de acordo com a fase da doença e sua causa, além das anormalidades no sedimento urinário, alteração em exame de imagem renal e determinação da taxa filtração glomerular (TFG) 1,7 . A última fase, conhecida como crônica é representada com a incompatibilidade dos rins com a vida, perdendo totalmente a sua função e o controle com o meio interno, sendo necessário realizar terapia de substituição renal ou transplante, compreendendo a uma TFG inferior à 15 ml/min/1.73 m2 7 .…”
Section: Functional Capacity Analysis Using the Six Minute Walk Test (6mwt) In Chronic Renal Patients Introduçãounclassified